Pengaruh Green Marketing, Brand Image dan Product Quality Terhadap Keputusan Pembelian Tupperware di Kota Mataram - Ulyani, Ulfa; Mulyono, Lalu Edy Herman (Postgraduate, University of Mataram, 2024)
This research is backed by environmental issues and plastic waste that can cause damage to the environment, thus requiring environmentally friendly products that can reduce the use of single-use materials with good quality and safe for long- term use. This research aims to determine the influence of Green Marketing, Brand Image, and Product Quality on the purchasing decisions of Tupperware products in Mataram City. By using a sample of 100 respondents from Mataram city, this research found that Green Marketing has a positive and significant influence on purchasing decisions. Brand image has a positive and significant influence on purchasing decisions, while Product Quality does not show a significant influence. These results indicate that Green Marketing and brand image are effective in increasing purchasing decisions, while product quality may not be effective in increasing the purchase decisions of Tupperware products in Mataram city.